‫أثر ‬‫إدارة‬ ‫المعرفة‬ ‫في‬ ‫تحقيق‬ ‫الأهداف‬ ‫الاستراتيجية‬ ‫دراسة‬‫حالة‬ ‫‪:‬‬ ‫شركة‬ ‫سكر‬ ‫كنانة‬ ‫المحدودة‬ ‫(‬ ‫‪2010-2016‬‬‫م‬‫)‬ - ‫د‪.‬‬‫السماني‬ ‫محمدالغالي‬ ‫نور‬ ‫الدائم‬ (White Nile Journal for Studies and Research, 2017)
This research has discussed the problem in a main question about the range of knowledge administration contribution in achieving organization strategic goals? the main question is divided into sub questions of which , what is knowledge administration impact on achieving organization’s strategic goals .The research aims to study the labor decreasing effect on organizations knowledge balance and the effect on the organization ability on achieving its strategic goals , recognizing intellectual capital concepts and its effect on achieving organization’s goals. From the research hypothesis, there is relation between the organization knowledge administration efficiency and achieving its strategic goals, there is a statistical relation between labor decreasing and intellectual capital and the ability to achieve goals .The researcher has used the historical method for previous studies that related to research subject , the descriptive method to describe of the phenomena, the subject of study. ‫‪ ‫‪